Impact of COVID-19 pandemic on sports and arthroscopic surgery in local hospitals - Wai Kiu Thomas Liu; Tak Man Wong (Journal of Orthopaedics, Trauma and Rehabilitation)
Introduction: Elective orthopaedic service has been reduced during the COVID-19 pandemic, and sports activities of the population have been minimised due to the social distancing strategies. This study aimed to quantify the change in sports medicine operations and its distributions during the COVID-19 pandemic, which could be useful for healthcare providers and policymakers plan in terms of resource planning in case of another severe infection outbreak in the future. Methods: Data, including age and gender of the patients and the types of operation, of all the surgeries performed by the Division of Sports and Arthroscopic Surgery in our institution from September 2017 to June 2022 was retrieved. The first 29 months of the 58 months period were classified as pre-COVID-19. Result: During the COVID-19 pandemic, there was a 20.9% reduction in the total number of sports and arthroscopic surgeries performed, from 10.1 to 8.0 per month ( p  = 0.042). The number of shoulder operations was significantly reduced by 32% ( p  = 0.029), with rotator cuff surgery reduced by 42% ( p  = 0.022). The number of knee operations decreased by 15% ( p  = 0.278), with anterior cruciate ligament (ACL) surgery reduced by 20% ( p  = 0.093). Notably, the relative proportion of knee and shoulder operations, as well as the patient demographics, remained similar during the COVID-19 pandemic. Conclusion: The reduction in the number of ACL and rotator cuff surgeries could be related to the reduced sports activity and manual labour activity during the lockdown periods of the pandemic. This study provides information and insight into the demand for sports medicine-related operations during the pandemic. It may be practical to limit elective operation sessions for sports and arthroscopic surgery during the pandemic, especially when resources are scarce. However, it is essential to strike a good balance between providing necessary care for patients who require these surgeries, while also taking appropriate measures to combat the pandemic.